PROBLEMS OF IMPROVING AGROCLUSTER ENTERPRISES AND ITS MANAGEMENT IN THE DEVELOPMENT OF THE FRUIT AND VEGETABLE NETWORK IN UZBEKISTAN (American Journal of Business Management, Economics and Banking, 2023)
Providing the population of Uzbekistan with food products and ensuring economic growth through the export of fruits and vegetables to the world market is one of the pressing issues of our time. This article reveals the importance of the development of fruit and vegetable growing and viticulture in our country, including in the Andijan region, and the features of improving the management system in the activities of enterprises of the fruit and vegetable cluster in this area, and also emphasizes the importance of regulatory documents for the development of the industry and the importance of the ongoing with this work.